Standardized treatment to improve hypertension control in primary health care: The HEARTS in the Americas Initiative. Issue 12 (12th October 2020) - DiPette, Donald J.; Goughnour, Kenneth; Zuniga, Eric; Skeete, Jamario; Ridley, Emily; Angell, Sonia; Brettler, Jeffrey; Campbell, Norm R. C.; Coca, Antionio; Connell, Kenneth; Doon, Rohit; Jaffe, Marc; et al.
Abstract: Hypertension is the leading risk factor for cardiovascular disease (CVD) worldwide. Despite the availability of effective antihypertensive medications, the control of hypertension at a global level is dismal, and consequently, the CVD burden continues to increase. In response, countries in Latin America and the Caribbean are implementing the HEARTS in the Americas, a community‐based program that focuses on increasing hypertension control and CVD secondary prevention through risk factor mitigation. One key pillar is the implementation of a standardized hypertension treatment protocol supported by a small, high‐quality formulary. This manuscript describes the methodology used by the HEARTS in the Americas program to implement a population‐based standardized hypertension treatment protocol. It is rooted in a seamless transition from existing treatment practices to best practice using pharmacologic protocols built around a core set of ideal antihypertensive medications. In alignment with recent major hypertension guidelines, the HEARTS in the Americas protocols call for the rapid control of blood pressure, through the use of two antihypertensive medications, preferably in the form of a single pill, fixed‐dose combination, in the initial treatment of hypertension. To date, the HEARTS in the Americas program has seen the improvement in antihypertensive medication formularies and the establishment of pharmacologic treatment protocols tailored to individual participating countries. This has translated to significant increases in hypertension control rates post‐program implementation in these jurisdictions. Thus, the HEARTS in the Americas program could serve as a model, for not only the Americas Region but globally, and ultimately decrease the burden of CVD.